A Comparison of Bit Serial and Bit Parallel DCT Designs. Issue 1 (1995) - Crook, David; Fulcher, John
Abstract : Bit parallel and bit serial VLSI designs for performing 1-dimensional Discrete Cosine Transforms are compared, in terms of size, complexity and throughput. It is concluded that the bit serial approach is more suited to this application, given the limitations of not only the available VLSI design tools, but also the available silicon real estate allocated for final chip fabrication.